Government of Tripura Draft Annual Plan 2006-2007 (Write-Up) Planning (P&C) Department - Planning Commission (Planning Commission, 2006)
Tripura with its geographical area of 10,492 sq. km. is flanked by Bangladesh on all 3 sides with a small corridor bordering Assam and Mizoram on the North Eastern Region of the State. The State is characterized by hilly terrain endowed with vast green forest. The erstwhile princely State merged with Indian Union on October 15, 1949 as C Category State and became Union Territory on 1st July 1963. Tripura became a full- fledged State on 21st January, 1972. Presently the State has four Districts, 15 Sub-Divisions, 40 development Blocks and has also one Autonomous District Council. Roughly 2/3rd of total area of the State is hilly. The six major hill ranges, Jumpui, Sakhangtang, Longtharai, Atharamura, Barmura, Debtamura and Kalajhari run north south of the State and are interspersed by velleys through which flow the major rivers of the State Gumti, Howrah, Dhalai, Feni and Jun which swell in monsoon but become shallow during the rest of the year.
Write-Up
Government of Tripura